Recycling of Reclaimed Asphalt Concrete Using Warm Asphalt Mixture and Emulsified Asphalt Cationic (Journal of Engineering, 2016)
Warm asphalt mixture (WMA) and reclaimed asphalt pavement (RAP) are the most memorable sustainable materials in world of asphalt concrete pavements . This research aims to study the warm asphalt mixture for different types of filler materials such as ordinary cement and limestone dust. Beside, this research focused on the test of emulsified asphalt properties by evaluating the performance of warm asphalt mixture by Marshall Stability properties as well as moisture sensitivity. The results of this experiment provided many important points. First, The cationic emulsified asphalt is suitable with RAP aggregate for production warm asphalt mixtures .Second, The effective mixing procedure for warm asphalt mixtures consists heating the RAP aggregate at 100 Co and then mixing with emulsified asphalt. Because of heating of reclaimed asphalt pavement material can improve the dispersion as well as densification significantly. Furthermore, the warm asphalt mixtures containing filler of cement type improved the Moisture sensitivity  performance by mean of increasing tensile strength   ratio furthermore enhanced Marshall properties .Finally, It was indicated that optimum asphalt content  (2.8%) is the best percentage found based on trail mixes ranging from (1.8 to 3.8) %